Drama dalam Pembelajaran Bahasa Inggris: Tantangan dan Harapan - Trisnian Ifianti (ALFABETA: Jurnal Bahasa, Sastra, dan Pembelajarannya, 2022)
Literature is believed to be a medium in language learning. Literary works can also foster motivation to read, write and improve students' speaking skills in achieving academic success. Poetry, prose and drama as literary works can be said to have a big role in developing students' literacy competence. This study discusses the teaching of drama as a literary work in the EFL class .It also describes some of the benefits of using drama as a learning tool in EFL classrooms and proposes several forms of teaching and learning that can be used to teach students' literary competence in learning literature, particularly drama.